Perspectives on musical strategies of settlement and migration: four case studies from the Western Cape, South Africa - Jansen van Rensburg, Claudia Elizabeth (Stellenbosch : Stellenbosch University, 2017)
Thesis (DPhil)--Stellenbosch University, 2017.